Correlation between Plasma Osteopontin and Alkaline Phosphatase in Type 2 Diabetes Mellitus Patients - Josua TH Sinambela; M.I Diah Pramudianti; Dian Ariningrum (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Diabetes Mellitus (DM) is a chronic disease caused by pancreas the inability to produce insulin or ineffectively insulin use. Fracture risk in type 2 DM patients increases even though the bone density is normal. This study aimed to examine the correlation of osteopontin (OPN) and alkaline phosphatase (ALP) in type 2 DM patients. An observational analytical study was conducted in 73 type 2 DM patients in Dr. Moewardi Hospital, Surakarta from October to November 2018. The subjects were examined for blood pressure, fasting blood glucose, two hours postprandial blood glucose, HbA1c, OPN, and ALP levels. P-value <0.05 was statistically significant with a 95% confidence interval. Poorly controlled type 2 DM had higher OPN levels than well-controlled (20.5±2.8 vs. 14.8±3.1 ng/mL, p <0.001). The ALP concentration was also higher in poorly controlled type 2 DM patients (79.9±31.7 vs. 61.1±25 U/L, p=0.003). The levels of OPN and ALP were significantly correlated in type 2 diabetes (r=0.273; p=0.020) and in well-controlled patients (r=0.353; p=0.047) but no correlation was found in poorly controlled type 2 DM patients (r= -0.073; p= 0.652). In this study, a significant correlation was found between OPN and ALP in patients with type 2 DM and well-controlled. Further study involving healthy controls and bone ALP measurement is needed.